Data Compression Conference, 2003. Proceedings. DCC 2003
DOI: 10.1109/dcc.2003.1193997
|View full text |Cite
|
Sign up to set email alerts
|

Video compression with intra/inter mode switching and a dual frame buffer

Abstract: Video codecs that use motion compensation have recently achieved performance improvements from the use of intra/inter mode switching decisions within a ratedistortion framework. A separate development has involved the use of multiple frame prediction, in which more than one past reference frame is available for motion estimation. In this paper, we show that using a dual frame buffer (one short term frame and one long term frame available for prediction) together with intra/inter mode switching improves the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…Work on resilient video coding and transmission for packet lossy networks has primarily focused on minimizing the average expected distortion for a frame (or group of frames) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], [27]. In these approaches the end-to-end distortion is defined as…”
Section: Expected Distortion Metricsmentioning
confidence: 99%
“…Work on resilient video coding and transmission for packet lossy networks has primarily focused on minimizing the average expected distortion for a frame (or group of frames) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], [27]. In these approaches the end-to-end distortion is defined as…”
Section: Expected Distortion Metricsmentioning
confidence: 99%
“…We see that the omniscient concealer chooses the LT frame for concealment substantially less often when the LT frame is just a regular frame. In earlier work [14,15], we concluded that pulsing the quality of frames for use as long term reference frames can have a beneficial effect on lowering the overall average distortion of the sequence. Table 2 shows that pulsing the quality of long term reference frames can also provide an advantage for error concealment.…”
Section: Resultsmentioning
confidence: 99%
“…If the pulsed quality is too uneven, the effect may be irritating to the viewer. When used with restraint, it was shown in [14,15] that the pulsed quality provides an advantage in reducing the overall distortion of the dual frame coded sequence, while the pulsing itself is not perceptible. Since the high quality LT frame is attractive also for the concealer, pulsing the quality provides a concealment advantage to the decoder as well, which is equipped to take advantage of the high quality reference frames.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations